2015
DOI: 10.1039/c5ra07184d
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen production by aqueous-phase reforming of ethylene glycol over a Ni/Zn/Al derived hydrotalcite catalyst

Abstract: HT) with different Ni/Zn ratios have been prepared by a coprecipitation method. The properties and microstructure of Ni/Zn/Al-HT precursors and derived catalysts were characterized by X-ray diffraction (XRD), H 2 -temperature programmed reduction (TPR), N 2 physical adsorption analysis (BET), scanning electron microscopy (SEM) and particle size distribution. The results exhibited that the as-prepared samples consisted of a hydrotalcite phase and a ZnO phase, and Zn 2+ was introduced into the layers. At the rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 29 publications
1
18
0
Order By: Relevance
“…However, formation of acetol increased due to higher acidity of the catalyst [111]. NieSn and NieZn catalysts supported on hydrotalcite-like compounds were also applied in APR of ethylene glycol [37,76]. Ni/Sn/Al-HT and Ni/Zn/Al-HT showed high H 2 production rate and selectivity, as well as constant catalytic stability.…”
Section: Hydrogen Formationmentioning
confidence: 96%
“…However, formation of acetol increased due to higher acidity of the catalyst [111]. NieSn and NieZn catalysts supported on hydrotalcite-like compounds were also applied in APR of ethylene glycol [37,76]. Ni/Sn/Al-HT and Ni/Zn/Al-HT showed high H 2 production rate and selectivity, as well as constant catalytic stability.…”
Section: Hydrogen Formationmentioning
confidence: 96%
“…In a recent study, it was shown that the deactivation of Ni/CNF could be inhibited by adding potassium hydroxide to the feed. In two different works, it was established that NiZn and NiSn catalysts derived from hydrotalcite‐like materials were especially promising for producing H 2 ,. When APR of ethylene glycol was combined with the carbonation of KOH, it was possible to produce CO X ‐free H 2 using non‐pyrophoric Ni .…”
Section: Catalytic Studiesmentioning
confidence: 99%
“…After that, nitrogen was introduced into the autoclave, and the autoclave was flushed three times to remove the residue air. Then, the reaction was carried out at 225 • C under nitrogen pressure of 2.6 MPa for 2.5 h [47]. After reaction, the gas phases were collected using a gas collecting bag and detected using gas chromatography (Beifen GC-3420A, China) equipped with a Porapak Q column of 3 m and a 5A molecular sieve.…”
Section: Catalytic Testsmentioning
confidence: 99%
“…The conversion of ethylene glycol and selectivity of H 2 and alkane were calculated according to the following equation [47].…”
Section: Catalytic Testsmentioning
confidence: 99%